Testing for Structural Change in Cointegrated Relationships. Analysis of price-wages models for Poland and Hungary - Roberto Golinelli; Renzo Orsi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
In previous studies concerning short and long run relationships for price-wage models, the cointegration analysis has been developed assuming the existence of a unique cointegration parametrisation. These empirical results reveal the presence of significant relationships, both in the short and in the long run, among prices, wages, labour productivity and exchange rate. In this paper we intend to develop the possibility of a more general type of cointegration, allowing for a change at an unknown time period in the sample. At this end we will consider mainly the long run relationship among these variables using the testing procedure suggested by Gregory and Hansen (1996a, 1996b). This permits us to consider a multivariate extension of the endogenous break univariate approach and in the meanwhile this enables to test for cointegration in the presence of possible structural breaking cointegrated relationships under the alternative. The empirical analysis of a multivariate model for price-wage relationship both for Poland and Hungary, over the period 1970–1996, is presented and discussed.
Keywords: 330